Balloon dilation eustachian tuboplasty for dilatory dysfunction: Safety and efficacy analysis in an Australian cohort. Issue 7 (1st June 2021) - Cheng, Horace; Saxby, Alex; Jufas, Nicholas; Kong, Jonathan; Patel, Nirmal
Abstract: Background: Eustachian tube dysfunction (ETD) is a common clinical condition encountered by otolaryngologists. The severity and duration of symptoms range from the mild and transient to the chronic and severe along with secondary pathologies. Balloon dilation eustachian tuboplasty (BDET) as a treatment, was first described in 2010 and has been studied extensively. This study evaluates the efficacy and safety of BDET in an Australian cohort. Methods: Retrospective chart review on all patients who underwent BDET from September 2016 to March 2020 was performed. The Eustachian Tube Dysfunction Patient Questionnaire (ETDQ‐7) was chosen as the primary outcome measure. Secondary outcome measures included subjective global assessment of presenting symptoms, ability to perform Valsalva maneuver and tympanometry. Any complications related to the procedures were reported. Results: One hundred and nineteen eustachian tube operations were included in this study. The patient cohort showed statistically significant improvement of mean EDTQ‐7 score from 0.7 to 2.9. Improvement in EDTQ‐7 was achieved in 83.9% of the cases. All patients in the baro‐challenge‐induced subgroup achieved improvement in ETDQ‐7 score. Complete resolution of symptoms with an ETDQ <2.1 was achieved in 37.1% of the cohort. There were no adverse safety events associated with the procedures. Conclusion: BDET resulted in improvement of the EDTQ‐7 score in most of patients in this Australian cohort with no reported complications. BDET was most successful in baro‐challenge‐induced subgroup with universal improvement. Lower success rates were seen in patients with secondary pathology from their ETD. Abstract : Sixty‐two operations were included in this retrospective case series. The patient cohort showed statistically significant improvement of mean EDTQ‐7 score from 4.7 to 2.9 with improvement in EDTQ‐7 was achieved in 83.9% of the cases. There were no adverse safety events associated with the procedures.